2019
DOI: 10.1051/0004-6361/201833585
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between solar plage and network properties

Abstract: Aims. We compare the properties of kG magnetic structures in the solar network and in active region plage at high spatial resolution. Methods. Our analysis used six SP scans of the solar disc centre aboard Hinode SOT and inverted the obtained spectra of the photospheric 6302 Å line pair using the 2D SPINOR code. Results. Photospheric magnetic field concentrations in network and plage areas are on average 1.5 kG strong with inclinations of 10 • − 20 • , and have < 400 m/s internal and 2 − 3 km/s external downfl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 91 publications
(131 reference statements)
2
9
1
Order By: Relevance
“…The values of v turb that we find in the low chromosphere are between the upper limits (∼3 km s −1 ) derived from photospheric lines in plage (Buehler et al 2019), and the larger typical values (∼7 km s −1 ) of nonthermal broadening implied by the optically thin O i line (Carlsson et al 2015). Even if we correct the latter taking into account the much hotter chromospheric temperatures implied by the ALMA data, the nonthermal broadening component in the width of the O i line would decrease by less than 1 km s −1 .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The values of v turb that we find in the low chromosphere are between the upper limits (∼3 km s −1 ) derived from photospheric lines in plage (Buehler et al 2019), and the larger typical values (∼7 km s −1 ) of nonthermal broadening implied by the optically thin O i line (Carlsson et al 2015). Even if we correct the latter taking into account the much hotter chromospheric temperatures implied by the ALMA data, the nonthermal broadening component in the width of the O i line would decrease by less than 1 km s −1 .…”
Section: Discussionsupporting
confidence: 74%
“…Plage are bright patches in the solar atmosphere that are associated with concentrations of predominantly unipolar, vertical magnetic fields. Their study is important because they offer a way of investigating the interplay between magnetic flux emergence, dynamics, and energy deposition and transport to higher layers (e.g., Shine & Linsky 1974;Title et al 1992;Martínez Pillet et al 1997;Kostik & Khomenko 2012Buehler et al 2015Buehler et al , 2019De Pontieu et al 2003Chitta et al 2017). Carlsson et al (2015) reported on observations of a plage region in the ultraviolet (UV) with the Interface Region Imaging Spectrograph (IRIS, De Pontieu et al 2014), and showed that the chromospheric Mg ii h and k resonance lines are brighter and broader, and their central reversals are shallower (or absent) compared to quiet-Sun (QS) profiles, whereas the subordinate UV triplet lines (diagnostics of the low chromosphere, Pereira et al 2015) are usually in absorption, suggesting that plage have a hot (∼6000−6500 K) and dense chromosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although their analysis concentrated on the quiet Sun, their results for network regions can be compared with our simulation results for a plage, as both network and plage host kilogauss magnetic field concentrations and are shown to share similar velocities for equally sized magnetic patches (Buehler et al 2019). They suggested turbulence (generated due to shocks) as the possible source of the chromospheric high-frequency power rather than propagating waves.…”
Section: Resultsmentioning
confidence: 81%
“…As a consequence of this inclusion, the inversion problem has become a global problem, including simultaneously all pixels in the field-of-view (FOV), which are spatially-coupled by the telescope's PSF. A number of excellent publications that targeted the physics of the solar photosphere made use of the latter technique to study in detail plage (Buehler et al 2015(Buehler et al , 2019 ( Danilovic et al 2016a,b) by using Hinode SOT observations. One limitation in the implementation of van Noort ( 2012) is that both the data and the model must be given in the same discrete spatial grid and, at least in their applications, they only consider one degradation mechanism.…”
Section: Introductionmentioning
confidence: 99%